2007
DOI: 10.1093/nar/gkm581
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the G quartet forming semaphorin 3F RNA with the RGG box domain of the fragile X protein family

Abstract: Fragile X syndrome, the most common cause of inherited mental retardation, is caused by the transcriptional silencing of the fmr1 gene due to an unstable expansion of a CGG trinucleotide repeat and its subsequent hypermethylation in its 5′ UTR. This gene encodes for the fragile X mental retardation protein (FMRP), an RNA-binding protein that has been shown to use its RGG box domain to bind to G quartet-forming RNA. In this study, we performed a detailed analysis of the interactions between the FMRP RGG box dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
70
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 49 publications
6
70
1
Order By: Relevance
“…While the region N-terminal to the common DEAD-box motifs is highly variable in the sequences of Vas orthologs from different species, the presence of RGG repeats within that region is conserved; for example, zebrafish Vas contains nine such motifs, and human Vas (DDX4) contains four. Two RGG repeats are present in mammalian fragile X mental retardation protein (FMRP), and have been shown to specifically recognize a G quartet structure in semaphorin 3F RNA, indicating that this motif can discriminate among target RNAs (Menon and Mihailescu 2007). RGG repeats are often present in proteins that contain other RNA-binding domains; for example, Vas contains a DEAD-box signature, while FMRP contains two hnRNPK homology (KH) domains; thus it has been proposed that they serve an auxiliary role in RNA binding (McBride and Silver 2001).…”
Section: Discussionmentioning
confidence: 99%
“…While the region N-terminal to the common DEAD-box motifs is highly variable in the sequences of Vas orthologs from different species, the presence of RGG repeats within that region is conserved; for example, zebrafish Vas contains nine such motifs, and human Vas (DDX4) contains four. Two RGG repeats are present in mammalian fragile X mental retardation protein (FMRP), and have been shown to specifically recognize a G quartet structure in semaphorin 3F RNA, indicating that this motif can discriminate among target RNAs (Menon and Mihailescu 2007). RGG repeats are often present in proteins that contain other RNA-binding domains; for example, Vas contains a DEAD-box signature, while FMRP contains two hnRNPK homology (KH) domains; thus it has been proposed that they serve an auxiliary role in RNA binding (McBride and Silver 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring G-quadruplexes targeted by FMRP adopt multiple conformations and are challenging to study by structural methods (27,28). Therefore, detailed structural information about RGG recognition of G-quadruplexes has been mostly obtained from studies on sc1 RNA (21), the RNA selected against the entire human FMRP but shown to require only the RGG motif of the protein for high affinity and specific binding (29,37,38).…”
Section: Significancementioning
confidence: 99%
“…Some of these RNAs harbor motifs that may form G-quartets and G-quadruplexes in vivo (21, 25). Several mRNAs contain regions shown to form G-quadruplexes implicated in FMRP binding in vitro (21,24,(26)(27)(28)(29). Notably, binding of FMRP to G-rich RNAs in vitro requires only the RGG motif, which specifically interacts with natural and in vitro selected G-quadruplex-containing RNAs such as a 35-nucleotide sc1 RNA (21,(26)(27)(28)(29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 FMRP has been shown to use its RGG box domain to bind mRNA targets that form G-quadruplex structures. [11][12][13] A Gquadruplex is assembled from stacked G quartets that are formed by guanine residues arranged in a planar configuration by Hoogsteen-type hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%